(untitled) (Journal of Naval Architecture and Marine Engineering, 2015)
Resistance reduction in ship becomes an important issue to be investigated. Energy consumption and its efficiency are related toward drag reduction. Drag reduction in fluid flow can be obtained by providing polymer additives, coating, surfactants, fiber and special roughness on the surface hull. Fish skin surface coated with biopolymers viscous fluid (slime) is one method in frictional resistance reduction. The aim of this is to understanding the effect of drag reduction using eel slime biopolymer in unsymmetrical trimaran ship model. The Investigation was conducted using towing tank test with variation of velocity. The dimension of trimaran model are L = 2 m, B = 0.20 m and T = 0.065 m. The ship model resistance was precisely measured by a load cell transducer. The comparison of resistance on trimaran ship model coated and uncoated by eel slime are shown on the graph as a function of the total drag coefficient and Froude number. It is discovered the trimaran ship model by eel slime has higher drag reduction compared to trimaran with no eel slime at similar displacement. The result shows the drag reduction about 11 % at Fr 0.35.